2019
DOI: 10.1096/fj.201802585rr
|View full text |Cite
|
Sign up to set email alerts
|

Reduced asymmetric dimethylarginine accumulation through inhibition of the type I protein arginine methyltransferases promotes renal fibrosis in obstructed kidneys

Abstract: The role of asymmetric dimethylarginine (ADMA) in chronic kidney disease (CKD) is unclear. Through inhibition of type I protein arginine methyltransferases (PRMTs), a novel strategy, we aimed to determine the effect of ADMA on renal fibrosis and explore its underlying working mechanisms. After sham or unilateral ureter ligation (UUO) operation, 20–25 g male c57 mice were treated with vehicle or PT1001B, an inhibitor of type I PRMTs, for 13 d. Moreover, human kidney 2 (HK2) and normal rat kidney 49F (NRK‐49F) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 18 publications
(27 reference statements)
3
26
2
Order By: Relevance
“…Moreover, kidney-specific knockdown of Ddah1 or Ddah2 gene increased the amount of renal ADMA in UUO mice, which was correlated with the reduced expression of fibrotic markers or weakened Masson's staining at days 1 and 7 in UUO kidneys. Thus, we conclude that renal ADMA is antifibrotic, which is in line with the conclusion provided by previous in vitro studies or indirect evidence using type I PRMT inhibitors or kidney-specific deletion of Ddah1 gene in mouse models of renal fibrosis [8,12]. Interestingly, a recent study showed that reduction of renal ADMA levels by intrarenal injection of adenovirus-expressing DDAH-1 ameliorates diabetic nephropathy [14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, kidney-specific knockdown of Ddah1 or Ddah2 gene increased the amount of renal ADMA in UUO mice, which was correlated with the reduced expression of fibrotic markers or weakened Masson's staining at days 1 and 7 in UUO kidneys. Thus, we conclude that renal ADMA is antifibrotic, which is in line with the conclusion provided by previous in vitro studies or indirect evidence using type I PRMT inhibitors or kidney-specific deletion of Ddah1 gene in mouse models of renal fibrosis [8,12]. Interestingly, a recent study showed that reduction of renal ADMA levels by intrarenal injection of adenovirus-expressing DDAH-1 ameliorates diabetic nephropathy [14].…”
Section: Discussionsupporting
confidence: 91%
“…Several in vivo and clinical studies have indicated that circulating ADMA is a risk factor and profibrotic in CKDs [10,11]. However, our previous study showed that treatment with type I PRMT inhibitor reduced renal ADMA levels and promoted renal fibrosis, suggesting that renal ADMA is antifibrotic [12]. In agreement with this conclusion, Tomlinson et al [8] showed that kidney-specific knockout of Ddah1 gene increased renal accumulation of ADMA and attenuated renal fibrosis in two different mouse models of CKD.…”
mentioning
confidence: 60%
“…Thus, enzymatic activities of PRMTs and DDAHs counteractively regulate the level of ADMA [51,52,53,54]. Wu et al showed that a PRMT1 inhibitor increased ADMA concentration in a dose-dependent manner both in vitro and in unilateral ureter obstructed mouse kidneys [55]. Elevated levels of ADMA are found to associate with lower DDAH2 and higher PRMT1 in cell and animal models [56,57].…”
Section: Adma—the Small Molecule Metabolite Product Of Arginine Mementioning
confidence: 99%
“…In one case, concentrations of l -NMMA and ADMA were 5.2 and 5.0 µM in the endothelial cells [108]. Indeed, a recent study showed that effect of decreased ADMA correlates with enhanced NO concentration locally in renal tubules but not in the whole UUO kidney [55].…”
Section: Adma—the Small Molecule Metabolite Product Of Arginine Mementioning
confidence: 99%
“…From our previous study, we demonstrated that circulatory levels of ADMA were increased in the diabetic kidney disease and can be used as a potential biomarker for the prediction of diabetic kidney disease at an early stage 8 . But there are limited studies on causal role of ADMA in the pathogenesis of renal diseases 18 20 . In our present study we are delineating the molecular mechanisms by which ADMA causes kidney cell injury under high glucose condition.…”
Section: Discussionmentioning
confidence: 99%